Predictive Biomarker Panel in Proliferative Lupus Nephritis- Two-Dimensional Shotgun Proteomics (Iranian Journal of Kidney Diseases, 2021)
Introduction. Lupus nephritis (LN) is one of the most serious complications of systemic lupus erythematous (SLE). With no specific clinical or laboratory manifestation to predict response to treatment, this study was aimed to provide a panel of predictive biomarkers of response before initiation of treatment. Methods. Liquid chromatography tandem mass spectrometry (LC-MS/MS) analysis was performed on plasma and urine samples of 11 patients with biopsy proven proliferative LN at the time of biopsy. Unsupervised principal component analysis (PCA), orthogonal projection to latent structures discriminant analysis (OPLS-DA), gene ontology annotation and protein mapping were performed on 326 proteins in plasma and 1381 proteins in urine samples. Results. Samples of eight patients achieved complete remission and three reached partial remission were analyzed. The mean 24-hour protein excretion was 3259 mg/day and the mean eGFR was 87.73 cc/min. OPLS-DA analysis of plasma samples showed a clear discrimination for complete and partial remission patients. Twenty plasma proteins and ten urine proteins with the highest fold changes and AUCs were selected as candidate biomarkers (IGHV1-18, PI16, IGHD, C3, FCER2, EPS8L2, CTTN, BLVRB). This plasma and urine biomarker panel is involved in oxidative stress, acute inflammation, reduction in regulatory T cells, complement pathway consumption, and proximal tubule bicarbonate reclamation. Conclusion. Our suggested panel of plasma and urine biomarkers can precisely discriminate patients with possibility of complete response to treatment. It seems that the higher indices of inflammation will associate with better chance of achieving complete remission.